Case Report: Precision COVID-19 Immunization Strategy to Overcome Individual Fragility: A Case of Generalized Lipodystrophy Type 4 - Zaffina, Salvatore; Piano Mortari, Eva; Di Prinzio, Reparata Rosa; Cappa, Marco; Novelli, Antonio; Agolini, Emanuele; Raponi, Massimiliano; Dallapiccola, Bruno; Locatelli, Franco; Perno, Carlo Federico; Carsetti, Rita (Frontiers in Immunology, 2022)
A 48-year-old patient affected with congenital generalized lipodystrophy type 4 failed to respond to two doses of the BNT162b2 vaccine, consisting of lipid nanoparticle encapsulated mRNA. As the disease is caused by biallelic variants of CAVIN1, a molecule indispensable for lipid endocytosis and regulation, we complemented the vaccination cycle with a single dose of the Ad26.COV2 vaccine. Adenovirus-based vaccine entry is mediated by the interaction with adenovirus receptors and transport occurs in clathrin-coated pits. Ten days after Ad26.COV2 administration, S- and RBD-specific antibodies and high-affinity memory B cells increased significantly to values close to those observed in Health Care Worker controls.